2015
DOI: 10.1007/s00236-015-0236-z
|View full text |Cite
|
Sign up to set email alerts
|

Guiding Craig interpolation with domain-specific abstractions

Abstract: PostprintThis is the accepted version of a paper published in Acta Informatica. This paper has been peerreviewed but does not include the final publisher proof-corrections or journal pagination.Citation for the original published paper (version of record):Leroux, J., Rümmer, P., Subotic, P. (2016) Guiding Craig interpolation with domain-specific abstractions. Abstract Craig Interpolation is a standard method to construct and refine abstractions in model checking. To obtain abstractions that are suitable for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…Eldarica uses interpolation abstraction [18] as a semantic way to guide the interpolation procedure towards "good" interpolants; in this method, interpolation queries are instrumented to restrict the symbols that can occur in interpolants, ranking the interpolants with the help of templates. It has previously been shown that interpolation abstraction can significantly improve the performance of Horn solvers [18].…”
Section: Craig Interpolation With Templatesmentioning
confidence: 99%
See 4 more Smart Citations
“…Eldarica uses interpolation abstraction [18] as a semantic way to guide the interpolation procedure towards "good" interpolants; in this method, interpolation queries are instrumented to restrict the symbols that can occur in interpolants, ranking the interpolants with the help of templates. It has previously been shown that interpolation abstraction can significantly improve the performance of Horn solvers [18].…”
Section: Craig Interpolation With Templatesmentioning
confidence: 99%
“…Picking the right predicates, either upfront or dynamically during analysis [5], is essential in this setting to ensure rapid convergence of a model checker, and is in practice achieved through a combination of "systematic" methods (for CEGAR, in particular through Craig interpolation) and heuristics. For instance, SLAM extracts refinement predicates from counterexamples using domain-specific heuristics [16]; YOGI uses machine learning to choose the default set of heuristics for picking predicates [19]; CPAchecker uses domain types to decide whether to represent variables explicitly or using BDDs [2], and to choose refinement predicates [4]; and Eldarica uses heuristics to guide the process of Craig interpolation [18]. Similar heuristics can be identified in tools based on abstract interpretation, among others.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations